Diskriminasi dalam Penyewaan Kos di Yogyakarta: Analisis Stereotip terhadap Masyarakat Timur Indonesia - Ramadhan, M. Panji; Hakim, Lukman (CV. ITTC INDONESIA, 2025)
This study examines the phenomenon of discrimination in boarding house rentals in Yogyakarta against people from Eastern Indonesia. The issue raised is the explicit rejection by boarding house owners of tenants from Eastern Indonesia based on negative stereotypes prevalent in society. The study aims to uncover the forms of discrimination occurring, identify the contributing factors, and describe the impact of such discrimination on the social life of Eastern Indonesian communities in Yogyakarta.This research employs a descriptive qualitative method with an interpretative approach. Data were collected through semi-structured interviews and direct observation of rental practices, focusing on interactions among boarding house owners, neighborhood heads (RT/RW), and prospective tenants from Eastern Indonesia. The collected data were analyzed thematically using the Braun & Clarke model to identify patterns of discrimination and the processes through which stereotypes are constructed in daily life.The findings reveal direct discrimination in the form of verbal rejection and digital advertisements explicitly stating restrictions against Eastern Indonesians. The stereotypes depict Eastern individuals as noisy, and troublesome largely shaped by mass media portrayals. The impacts of this discrimination include social injustice, alienation, cultural exclusion, and threats to the values of inclusivity and diversity in Yogyakarta. This study emphasizes the importance of policy intervention, strengthened public education, and media responsibility in creating fair and balanced representations.